Animals, gods and men from East to West : papers on archaeology and history in honour of Roberta Venco Ricciardi - Peruzzetto, Alessandra.; Dorna Metzger, Francesca.; Dirven, Lucinda.; Ricciardi, Roberta Venco. (BAR international series ;)
The 21 articles collected in this commemorative volume centre on animals in relation to men and gods.